Health decision making and behavior: The role of affect‐laden constructs. Issue 8 (August 2017) - Magnan, Renee E.; Shorey Fennell, Bethany R.; Brady, Jacquelyn M.
Abstract: A common criticism of social cognitive models predicting health behavior is their exclusion of affect—an important component of individual‐level decision processes for behavior change. Yet the role of affect, and its interaction with cognitions, is complex. We provide an overview of affect and pathways through which it is proposed to influence outcomes. Then, we discuss several common social cognitive models of health behavior change. Next, we highlight specific affect‐laden constructs (those that incorporate affective and cognitive components) related to health behavior change. We aim to provide clarity on terminology and measurement of the affect‐laden constructs and evidence associating them with health behavior. Finally, we discuss strategies for incorporating these constructs within popular cognitive‐based theories and provide suggestions for future work.